Novel Small Antimicrobial Peptides Extracted from Agricultural Wastes Act against Phytopathogens but Not Rhizobacteria - Thitiporn Ditsawanon; Sittiruk Roytrakul; Narumon Phaonakrop; Sawanya Charoenlappanit; Siriwan Thaisakun; Nonglak Parinthawong (Agronomy, 2022)
Nonedible materials such as agricultural wastes can serve as sources of antimicrobial peptides (AMPs) effective against bacterial plant pathogens. In this study, thirteen agricultural samples were collected and their protein hydrolysates obtained using pepsin. Peptides smaller than 3 kDa were purified by reverse-phase chromatography, cation exchange chromatography, and pI-based fractionation and tested for activity against plant pathogenic bacteria at each step. Active peptides were then analyzed for putative mechanisms using nanoLC–MS/MS and the Mascot program. Ultimately, eight candidate peptides originating from bagasse were selected and chemically synthesized for a comparative study of growth inhibition in plant pathogenic bacteria and plant growth-promoting rhizobacteria (PGPRs). Three synthesized peptides exhibited a potent activity against plant pathogenic bacteria while also supporting the growth of PGPRs. Proteomics analysis revealed the peptides PQLAVF (Pro-Gln-Leu-Ala-Val-Phe) and MDRFL (Met-Asp-Arg-Phe-Leu) to act against Xanthomonas oryzae pv. oryzae via membrane-active mechanisms, while peptide VQLMNSL (Val-Gln-Leu-Met-Asn-Ser-Leu) acted against Pectobacterium carotovorum and Agrobacterium rhizogenes through intracellular-active mechanisms. Further study remains necessary to customize peptides by amino acid substitution not only for a higher effective activity against these and other critical pathogens, but also for a higher stability of peptides in critical condition when applied in industrial processes in the future.
Keywords: Antimicrobial Peptides and Activities; Probiotics and Fermented Foods; Transgenic Plants and Applications